Congenital Hemangiopericytoma (Journal of Medicine, 2011)
Hemangiopericytoma is a rare vascular neoplasm that usually occurs in adults. Occurrence of the tumors in infants, known as congenital or infantile hemangiopericytoma, is rare and its behavior is different than that of adult type. We are reporting a 10 day old male neonate presenting with a mass on his left arm since birth. Clinically it was suspected as lymphangioma because of its high incidence in pediatric patients. The tumor was surgically removed and histopathologically diagnosed as a case of hemangiopericytoma. Keyword: Hemangiopericytoma; congenital type. DOI: 10.3329/jom.v12i1.6937J Medicine 2011; 12 : 89-90